The agony of Spain : socialist appeal to British Democracy : [speech] : Senora de Palencia, Senor de Asua - Palencia, Isabel de (1878-1974); Jiménez de Asúa, Luis (1889-1970)
Tít. tomado de la cub.En la cub.: "Spanish envoys tell the facts" y foto del Daily Herald de los conferenciantes